High-resolution 3D ultrastructural analysis of developing mouse neocortex reveals long slender processes of endothelial cells that enter neural cells - Wilsch-Bräuninger, Michaela; Peters, Jula; Huttner, Wieland B. (Frontiers in Cell and Developmental Biology, 2024)
The development of the neocortex involves an interplay between neural cells and the vasculature. However, little is known about this interplay at the ultrastructural level. To gain a 3D insight into the ultrastructure of the developing neocortex, we have analyzed the embryonic mouse neocortex by serial block-face scanning electron microscopy (SBF-SEM). In this study, we report a first set of findings that focus on the interaction of blood vessels, notably endothelial tip cells (ETCs), and the neural cells in this tissue. A key observation was that the processes of ETCs, located either in the ventricular zone (VZ) or subventricular zone (SVZ)/intermediate zone (IZ), can enter, traverse the cytoplasm, and even exit via deep plasma membrane invaginations of the host cells, including apical progenitors (APs), basal progenitors (BPs), and newborn neurons. More than half of the ETC processes were found to enter the neural cells. Striking examples of this ETC process “invasion” were (i) protrusions of apical progenitors or newborn basal progenitors into the ventricular lumen that contained an ETC process inside and (ii) ETC process-containing protrusions of neurons that penetrated other neurons. Our observations reveal a — so far unknown — complexity of the ETC–neural cell interaction.